Accounting Review of Recording of Joper Chicken Inventory as a Biological Asset Based on PSAK 69 - Dara Nida Utamie; Puja Fitratunnisa (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Small-scale poultry farmers like CV Almarn Ligurbar Farm typically do not classify chickens as biological assets in accordance with PSAK 69. This results in financial statements inaccurately reflecting their actual economic worth. This study aims to analyze the method of recording chicken inventory that meets the PSAK 69 standards regarding biological assets, analyzing the differences between the recording practices carried out and the standards set out in PSAK 69.  PSAK 69 requires the measurement of biological assets using fair value less costs to sell. This study was conducted on small-scale chicken farmers, namely CV Almarn Ligurbar Farm. This study uses a descriptive qualitative approach with a case study method. The results of the study indicate that farmers have not fully implemented PSAK 69 due to limitations in understanding accounting standards, lack of financial records, and uncertainty in market prices. Recording is not carried out as chickens as biological assets during their growth period at CV Almarn Ligurbarn Farm, which has a significant impact on the validity and reliability of the resulting financial statements. Based on PSAK 69, chickens in the care process including the initial, intermediate, and pre-harvest phases are recognized as active biological assets that experience changes in both quantity and quality, so they should be recognized and valued in accounting. However, the reality in the field indicates that these chickens are seen only as part of the production process, without official recognition as assets in the statement of financial position.